Radiation Pasteurization of Food - Thayer, Donald W.; Josephson, Edward S.; Brynjolfsson, Ari; Giddings, George G. (Council for Agricultural Science and Technology (CAST), 1996)
Foodborne bacteria cause as many as 9,000 deaths in the United States annually; yet scientifically proven safe, low doses of pasteurizing radiation can kill over 99% of most foodborne bacteria. Radiation pasteurization safely controls foodborne pathogens on beef, pork, lamb, and seafood. Long-term animal feeding studies have demonstrated that radiation pasteurized or sterilized foods are safe and nutritious for humans. The process has been endorsed by the U.S. FDA, the USDA, the World Health Organization, the health authorities of 40 countries, and many other associations.